Characteristics and Patterns of Cigarette Smoking and Vaping By Past-Year Smokers Who Reported Using Electronic Nicotine Delivery System to Help Quit Smoking in the Past Year: Findings From the 2018–2019 Tobacco Use Supplement to the Current Population Survey. Issue 3 (17th August 2022) - Chang, Joanne T; Mayer, Margaret; Jackson, Rebecca A; Rostron, Brian L; Coleman, Blair; Lee, Terrence; Ambrose, Bridget K; Chang, Cindy M
Abstract: Introduction: Cigarette smoking has declined, while electronic nicotine delivery system (ENDS) use has increased in the United States. Understanding the role of ENDS in adult smoking quit attempts and cessation is important for estimating their population health impact. Aims and Methods: We used data from 2018 to 2019 tobacco use supplement to the current population survey to examine demographic characteristics and ENDS use patterns among adult ENDS users who reported quitting smoking in the past year by trying to switch to ENDS ("switchers") and smokers who did or did not make a quit attempt in the past year. χ 2 tests of proportions and t -tests were used to compare characteristics between groups. Results: In 2018–2019, about three-quarters of switchers reported daily use of ENDS compared to only one-third of dual users with a recent quit attempt by trying to switch to ENDS. Compared to dual users who made a quit attempt by trying to switch to ENDS, switchers were more likely to use menthol/mint-flavored ENDS exclusively (5.6% vs. 13.1%; p  = .004) but less likely to use tobacco-flavored ENDS exclusively (21.2% vs. 13.7%; p  = .01). Conclusions: ENDS users who quit smoking in the past year and reported trying to quit by switching to ENDS were more likely to use menthol/mint flavors exclusively and use ENDS daily compared to dual users who made a quit attempt by trying to switch to ENDS. Longer-term prospective data may better clarify the role of ENDS in smoking quit attempts and cessation. Implications: This study provides information on patterns of ENDS use in former smokers and current smokers who tried to quit smoking by switching to ENDS in a national sample of U.S. adults. These results can inform policy actions concerning ENDS products.